2019
DOI: 10.15361/1984-5529.2019v47n1p83-90
|View full text |Cite
|
Sign up to set email alerts
|

Genetic divergence between pepper accessions based on quantitative fruit traits

Abstract: The development of new Capsicum cultivars aiming to meet market requirements will depend, above all, on the genetic diversity of the study population. To quantify this genetic divergence, several multivariate techniques assessing quantitative traits have been employed. This study aimed to: i. estimate the genetic diversity among Capsicum chinense accessions from the Active Germplasm Bank of Plants of the Federal University of Viçosa (BGH-UFV); ii. indicate promising accessions for prospective studies of specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The PCA results showed that among the variables analyzed those with the most significance greater than 5% were FTSh (6.32%), MFC (7.41%), FSH (10.51%), CCS (11.56%) and IFC (49.49%). For Capsicum breeding, crosses between genetically divergent genotypes are recommended and it is desirable that both parents are high yielding and complementary in terms of fruit quality traits [15,30]. In this case, the characterization of "pimenta-de-cheiro" C. chinense genotypes and their allocation in different clusters, based on multivariate analyses will be important to guide future crosses.…”
Section: Morpho-agronomic Characterization Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The PCA results showed that among the variables analyzed those with the most significance greater than 5% were FTSh (6.32%), MFC (7.41%), FSH (10.51%), CCS (11.56%) and IFC (49.49%). For Capsicum breeding, crosses between genetically divergent genotypes are recommended and it is desirable that both parents are high yielding and complementary in terms of fruit quality traits [15,30]. In this case, the characterization of "pimenta-de-cheiro" C. chinense genotypes and their allocation in different clusters, based on multivariate analyses will be important to guide future crosses.…”
Section: Morpho-agronomic Characterization Datamentioning
confidence: 99%
“…For an effective use of genetic resources, genes of interest for genetic breeding, their adequate characterization, evaluation, and documentation are essential, as are studies that elucidate the genetic basis of the selection target trait directed towards the establishment of efficient strategies in breeding programs [14][15][16][17]. The characterization of genotypes with recommended descriptors can provide studies of sampling, selection, and hybridization to define adequate strategies for the conservation and genetic breeding of C. chinense.…”
Section: Introductionmentioning
confidence: 99%